Historical Perspectives on Family Hunting Territories in Eastern James Bay - Morantz, Toby (Anthropologica, 2022)
The relatively extensive literature developed over the past seventy years has made it possible to analyze the component features of what has come to be termed the "family hunting territory system." By using the observational data found in the eighteenth-, nineteenth-, and twentieth-century records of the Hudson's Bay Company for eastern James Bay, most of these features were isolated. Given this historical context, the arguments presented in favor of early or recent development of such a land tenure system were examined and assessed. An attempt has been made to explain the role of the fur trade in this earlier development.